To transform the equation \(-2y = 14 - 6x\) into slope-intercept form (which is \(y = mx + b\), where \(m\) is the slope and \(b\) is the y-intercept), follow these steps:
- First, isolate \(y\) on one side of the equation. Start by dividing both sides by \(-2\):
\[ y = \frac{14 - 6x}{-2} \]
- Distribute the division on the right side:
\[ y = \frac{14}{-2} - \frac{6x}{-2} \]
This simplifies to:
\[ y = -7 + 3x \]
- Rearranging gives us:
\[ y = 3x - 7 \]
Now the equation is in slope-intercept form:
\[ y = 3x - 7 \]
Here, the slope \(m\) is 3, and the y-intercept \(b\) is -7.